2018
DOI: 10.1007/s00246-018-1950-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of Speckle Tracking Echocardiography to Assess Left Ventricular Systolic Function in Patients with Surgically Repaired Tetralogy of Fallot: Global and Segmental Assessment

Abstract: Patients with repaired Tetralogy of Fallot (rToF) can have significant right and left ventricular dysfunction which can impact clinical outcome. Conventional echocardiographic evaluation using ejection fraction can be limited in detecting early stages of deteriorating left ventricular (LV) systolic function. Speckle-tracking echocardiography (STE) provides a promising emerging tool for early detection of LV systolic dysfunction. The aim of this cross-sectional study is to evaluate the left ventricular global a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…One study showed that asymptomatic paediatric TOF population with a normal LV EF already exhibited abnormal segmental and global LV longitudinal and circumferential strains compared with a matched healthy control group. 19 Interestingly, our study showed that male patients with TOF had worse RV function compared with female patients at long-term follow-up. This finding supports previous findings of Menting et al as they showed that male patients with TOF had significantly lower LV GLS and RV free wall strain compared with female patients and speculated that RV dysfunction adversely affects LV function, probably by mechanical coupling of the ventricles.…”
Section: Heart Failure Outcomementioning
confidence: 51%
See 1 more Smart Citation
“…One study showed that asymptomatic paediatric TOF population with a normal LV EF already exhibited abnormal segmental and global LV longitudinal and circumferential strains compared with a matched healthy control group. 19 Interestingly, our study showed that male patients with TOF had worse RV function compared with female patients at long-term follow-up. This finding supports previous findings of Menting et al as they showed that male patients with TOF had significantly lower LV GLS and RV free wall strain compared with female patients and speculated that RV dysfunction adversely affects LV function, probably by mechanical coupling of the ventricles.…”
Section: Heart Failure Outcomementioning
confidence: 51%
“…One study showed that asymptomatic paediatric TOF population with a normal LV EF already exhibited abnormal segmental and global LV longitudinal and circumferential strains compared with a matched healthy control group. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Such nding reveals the limitation of routine 2D echocardiography to assess and follow up of left ventricle function in these groups of patients. Speckle tracking echocardiography is more sensitive to the detection of left ventricle abnormalities than 2D echocardiography (3,15,(18)(19)(20)(21)(22)(23), and with regarding our nding it may be useful to unmask left ventricle dysfunction in the setting of repaired Tetralogy of Fallot follow up. Although to evaluate this hypothesis, we suppose more studies and prospective analysis of Speckle tracking echocardiography role in repaired Tetralogy of Fallot patients.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to changes in myocardial architecture, other factors including hypertrophy and hypoxic condition before corrective surgery, probable intraoperative myocardial damage, and pulmonary regurgitation following surgical repair contribute to postoperative ventricular dysfunction. It has been shown that transventricular incision for closing ventricular septal defect and relief of right ventricular outflow tract obstruction in TOF children increases the rate of late right ventricular dysfunction and worsens the long‐term clinical outcomes 1,14 . Furthermore, severe pulmonary regurgitation can put a volume overload on the right ventricle that may adversely affect the right ventricle systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Also, TOF children with double outlet right ventricle, atrioventricular septal defect or Secundum atrial septal defect, genetic syndromes, and postoperative complications were excluded from the study. The sample size was calculated based on the prior study by Mohammad Nijres et al 14 reporting means of global circumferential left ventricular strain in repaired TOF patients (−17.24) and control group (−22.74). Hence, the estimated sample size for each group was 18 based on a type I error of 5%, power of 90%, and a formula for comparing means between two groups.…”
Section: Methodsmentioning
confidence: 99%